Hathor im Pflanzendickicht: Zum Menit des libyschen Großfürsten Ker. (Ägyptisches Museum Berlin Inv. 8939) - Moje, Jan (Zeitschrift für ägyptische Sprache und Altertumskunde, 2012)
Publication and socio-cultural analysis of a faience menit belonging to the Libyan Great Chief of the Libu and Meshwesh, Ker, from the Western Delta.